Research on the Application Scenarios of Central Bank Digital Currency - Liu, Yilu (International Journal of Global Economics and Management, 2024)
Central Bank Digital Currency (CBDC), as a new form of legal tender, has attracted widespread attention worldwide. From the theoretical and empirical perspectives, this paper systematically analyzes the potential of CBDC in different application scenarios, its implementation effects and the challenges it faces, and puts forward corresponding suggestions. It is found that CBDC has a wide range of application prospects in the fields of cross-border payment, real-time payment, offline payment, securities settlement, etc., but it also faces challenges in technical implementation, legal regulation, privacy protection and financial stability.